2006
DOI: 10.1128/jcm.44.3.1132-1134.2006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Bocavirus in Japanese Children with Lower Respiratory Tract Infections

Abstract: Human bocavirus (HBoV), a newly cloned human virus of the genus Bocavirus, was detected by PCR from nasopharyngeal swab samples (8 of 318; 5.7%) collected from children with lower respiratory tract infections. HBoV may be one of the causative agents of lower respiratory tract infections in young children.The family Parvoviridae contains two subfamilies: Parvovirinae, which infects vertebrates, and Densovirinae, which infects insects. The subfamily Parvovirinae consists of five genera: Parvovirus, Erythrovirus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

38
185
8
21

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 7 publications
38
185
8
21
Order By: Relevance
“…HBoV ile enfekte olgularımızın laboratuvar bulguları değerlendirildiğinde, lökosit sayısı ve CRP değerlerinde artış olduğu izlenmiş, ancak bu fark istatistiksel olarak anlamlı bulunmamıştır (Tablo IV). Bu bulgu, diğer araştırmacıların verileri ile uyumludur 34,36,40 . Yapılan çalışmalarda HBoV enfeksiyonlarında patolojik akciğer grafisi bulgusu oranları %43-83 arasında değişmektedir 36,41 .…”
Section: Discussionunclassified
“…HBoV ile enfekte olgularımızın laboratuvar bulguları değerlendirildiğinde, lökosit sayısı ve CRP değerlerinde artış olduğu izlenmiş, ancak bu fark istatistiksel olarak anlamlı bulunmamıştır (Tablo IV). Bu bulgu, diğer araştırmacıların verileri ile uyumludur 34,36,40 . Yapılan çalışmalarda HBoV enfeksiyonlarında patolojik akciğer grafisi bulgusu oranları %43-83 arasında değişmektedir 36,41 .…”
Section: Discussionunclassified
“…Although IgG antibody present in a single serum sample does not reflect an acute infection, a high rate of IgG positive sera from healthy children does suggest that HBoV infection is more common in children than genomic detection has shown previously (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). Infection with B19 occurs in children in a high incidence asymptomatically.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HBoV has been reported to be between 1.5% to 11.3% based on tests of respiratory samples from individuals with acute respiratory illness (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). HBoV appears to be associated with lower respiratory tract infections, and in many cases, co-infection with other respiratory viruses (Allander et al, 2007;Fry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2,3). Most prevalence studies were done on samples from children with respiratory tract diseases, with rates observed between 1.5-19% (1,(4)(5)(6)(7)(8)(9)(10)(11)(12). Studies made on fecal specimens indicate that HBoV is also prevalent in children with acute gastroenteritis, with 0.8-16% of samples being HBoV + (4,(13)(14)(15).…”
mentioning
confidence: 99%